Abdominal perfusion pressure is superior from intra-abdominal pressure to detect deterioration of renal perfusion in critically Ill patients - GÜL, FETHİ; ARSLANTAŞ, MUSTAFA KEMAL (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2019)
BACKGROUND: Intra-abdominal hypertension (IAH) is a frequent cause of acute kidney injury (AKI) among critically ill patients who have risk factors. This study aimed to determine the relation between Abdominal Perfusion Pressure (APP) and AKI showed by the Doppler-based renal resistive index (RRI). METHODS: In this study, 38 patients older than 18 years old who received mechanical ventilation and had risk factors for the development of IAH were prospectively studied. All measurements and parameters were divided into two groups according to renal dysfunction (Group I: RRI <0.72 vs Group II: RRI >0.72). RESULTS: The mean IAPs were not significant between the groups, 11.5 +/- 6.9 mm Hg in Group I (n=35) and 13.5 +/- 5.8 in Group II (n=33), respectively. APPs were statistically higher in Group I (81.2 +/- 13.6) than Group II (66.4 +/- 9.5) (p<0.001). The AUC for the association between APP at RRI >0.72 was 0.802 (p<0.001), with the APP <= 72 mmHg having a sensitivity of the 76% (95% CI 58-89%) and a specificity of 71% (95% CI 54-85%). CONCLUSION: Our findings suggest that an APP with a threshold of <= 72 mmHg is associated with a significant increase in renal RRI, which may be predictive of worsening of renal perfusion.
Keywords: Abdominal perfusion pressure; renal perfusion pressure; renal resistive index; ACUTE KIDNEY INJURY; COMPARTMENT SYNDROME; RESISTIVE INDEX; HYPERTENSION; ULTRASONOGRAPHY; SECONDARY